KKN Tematik Pemanfaatan Hutan Sebagai Resapan Air Dan Pencipta Iklim Mikro Di Desa Jolotundo - Churin'in, Rachma Arsyieta; Roidah, Ida Syamsu (Universitas Gajah Putih, Indonesia, 2023)
Forests have numerous benefits in life, including serving as water catchment areas and creating microclimates that play a crucial role in the growth of surrounding plants. The knowledge of utilizing these forests is still lacking among the residents of Jolotundo Village, resulting in minimal awareness of forest conservation, leading to crop failure. Crop failure is also caused by the lack of community awareness regarding environmental cleanliness, resulting in the presence of plastic waste in plantation and farming areas, which reduces the soil's ability to absorb nutrients and organic matter. Therefore, it is necessary to provide an exposition on the importance of forest utilization and environmental cleanliness to minimize crop failure. The objective of this activity is to enhance understanding of forest utilization and environmental cleanliness. The implementation of this activity will be carried out through a Community Service Program (KKN) in collaboration with Perhutani, consisting of preparation, execution, and evaluation. The program includes monitoring the previously planted bamboo plants by Perhutani and engaging in collective efforts to clean up plastic waste in bamboo forest, agricultural, and plantation areas. The activity ran smoothly, although the collective cleaning effort could not be optimally executed due to time constraints in the Community Service Program. Hutan memiliki banyak sekali manfaat dalam kehidupan, diantaranya adalah sebagai resapan air dan pencipta iklim mikro yang memegang peran penting dalam pertumbuhan tanaman sekitar. Pengetahuan akan pemanfaatan hutan ini masih tidak dimiliki oleh warga Desa Jolotundo, sehingga kesadaran akan menjaga hutan masih minim hingga menyebabkan gagal panen. Gagal panen juga diakibatkan karena kurangnya kesadaran masyarakat akan kebersihan lingkungan sehingga banyak ditemukan sampah plastik di area hutan perkebunan/bertanian yang menyebabkan berkurangnya kemampuan menyerap tanah dan zat organik. Oleh karena itu perlu dilakukan pemaparan tentang pentingnya pemanfaatan hutan dan kebersihan lingkungan sehingga mampu meminimalisir terjadinya gagal panen. Tujuan kegiatan ini adalah meningkatkan pemahaman tentang pemanfaatan hutan dan kebersihan lingkungan. Pelaksanaan kegiatan ini dilakukan melalui program KKN bekerjasama dengan Perhutani yang terdiri dari persiapan, pelaksanaan, dan evaluasi kegiatan. Program yang akan dilakukan adalah pengawasan terhadap tanaman bamboo yang sebelumnya sudah ditanam oleh pihak perhutani dan gotong royong pembersihan sampah plastik di lahan hutan bamboo, pertanian dan perkebunan. Kegiatan ini berjalan lancar namun kegiatan gotong royong pembersihan tidak dapat dilakukan secara optimal karena keterbatasan waktu KKN.